Risk of Diagnosed Adolescent-Onset Non-Affective Psychotic Disorder by Migration Background in British Columbia: A Retrospective Cohort Study. (January 2023) - Magee, Carly; Oberle, Eva; Guhn, Martin; Gadermann, Anne; Puyat, Joseph H.
Objective: We recently found that the risk of diagnosed non-affective psychotic disorder between the ages of 13 and 19 was lower for immigrant adolescents compared to those without a personal or parental migration history in British Columbia (BC), Canada. In the current study, we further examined the risk for migrants compared to non-migrants by region of origin and immigrant generation (first vs. second), adjusting for several demographic factors and migration class. Methods: Administrative data were used to construct a cohort of individuals born 1990–98 and residing in South-Western BC ( N = 193, 400). Cases were identified by either one hospitalization or two outpatient physician visits with a primary diagnosis of a non-affective psychotic disorder. Poisson regression was used to estimate incidence rate ratios (IRR) of a diagnosed non-affective psychotic disorder by region of origin among first- and second-generation migrants compared to non-migrants, adjusting for sex, birth year, neighbourhood income and low family income. Results: Risk of diagnosed non-affective psychotic disorder was lower among first-generation migrants from East Asia (IRR = 0.34[95% CI: 0.25–0.46]), South-Asia (IRR = 0.47[95% CI: 0.25–0.89]) and South-East Asia (IRR = 0.55[95% CI: 0.32–0.93]) and second-generation migrants from East Asia (IRR = 0.49[95% CI: 0.35–0.69]) and South Asia (IRR = 0.52[95% CI: 0.37–0.73]), compared to non-migrants. Adjusting for migration class attenuated but did not fully explain variation in risk by region among first-generation migrants. No groups exhibited a significantly elevated risk of the diagnosed non-affective psychotic disorder compared to non-migrants. Conclusion: Findings from this study underline the complexity of the association between migration and psychotic disorders. Future research should investigate why certain groups of migrants are less likely to be diagnosed and whether there are specific sub-groups that face an elevated risk.